Pelatihan Digital Marketing Untuk Meningkatkan Kesejahteraan Pengrajin Jamu Tradisiona Di O Mangunharjo - Ira Primalasari; Vera Octalia; Syabawaihi Syabawaihi (LP4MK STKIP PGRI Lubuklinggau, 2025)
Digital marketing training is a strategic approach to strengthen the capacity of micro, small, and medium enterprises (MSMEs), especially traditional herbal medicine craftsmen who face marketing challenges in the digital era. This study aims to evaluate the impact of digital marketing training on improving the economic welfare of herbal medicine craftsmen in O Mangunharjo. The study used a descriptive qualitative approach through participatory observation, in-depth interviews, and documentation studies. The results showed that the training not only improved online promotion skills but also built the confidence of business actors in facing a wider market. Digital marketing training has been shown to contribute to increasing income and the existence of local herbal medicine products on digital platforms. Keywords: digital marketing, welfare, traditional herbal medicine, MSMEs, O Mangunharjo